PERBEDAAN BERSEPEDA DAN BERJALAN KAKI KE SEKOLAH TERHADAP TINGKAT KEBUGARAN JASMANI SISWA (STUDI PADA SISWA KELAS VII SMP NEGERI 1 SEMPU KABUPATEN BANYUWANGI) - IQBAL ARYS AGUSTAVIAN, MUHAMMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Health is the basic humans needs. There is no doubt that physical needs are important in maintaining the health. The higher health level, the better physical fitness level. One purpose of physical, sport and health education is to improve the students’ physical fitness. Physical fitness is one’s physical ability in doing daily exercises optimally, even still be able to do another physical exercise without causing significant fatigue. The students’ physical fitness is affected by daily activities, whether in the school or out the school. In addition, student’s daily activities when they leave and go home which use the physical activities, such as go cycling and walking could affect students’ physical fitness. The research questions are: 1) Is there any differences between cycling and walking to the school toward students’ physical fitness level in seven grade of SMP Negeri 1 Sempu Kabupaten Banyuwangi? 2) To what extend is the differences between cycling with walking to the school toward students’ physical fitness level in seven grade of SMP Negeri 1 Sempu Kabupaten Banyuwangi? 3) If there is difference, which one is better, the physical fitness level of seven graders who go cycling or who go on foot to the SMP Negeri 1 Sempu Kabupaten Banyuwangi ? The sample of research is the purposive sampling. It is a sampling that the characteristics have been known according to the characteristics or natures of the population. Sampling is done by distributing the questionnaires so it will obtains the group of students who go cycling to the school and the group of students who go walking to the school. The Research method used is Descriptive Quantitative Method and t-test (Independent Sample t-test), while the process of collecting the data is done by using the MFT test. The result can be concluded as: 1) there are differences in the level of physical fitness between students who go cycling to the school with those who go walking to the school. It can be seen on the MTF result that the students who go cycling to the school have the average score as 37,121; standard deviations score as 6,2273; and variant score as 38,780; then the lowest score is 27,6 and the highest score is 47,9. While the MTF result of students that walks to the school have the average core as 43,584; standard deviations score as 8,7562; and variant score as 76,670; then the lowest score is 30,2 and the highest score is 55,7. From the analysis result of independent sample t-test (the test of average differences between the group), it is obtained: tcount (2,622) > ttable (1,684). In other words, there is significant difference in physical fitness level of students in seven grade of SMP Negeri 1 Sempu Kabupaten Banyuwangi who goes cycling to the school with those who walks to the school. 2) The result of average difference concludes that the physical fitness level which is measured in the MTF test from students who goes walks to the school is higher than the MTF test of students who goes cycling to the school with the percentage as 6,9%. Keywords : Physical Fitness, Students go cycling with goes walks to the school.